Conference of ministers of the West-European Union. F.l.t.r.: Longerstaey, v.d. Klaauw, ?, v.d. Mei
Conference of ministers of the West-European Union. F.l.t.r.: Longerstaey, v.d. Klaauw, ?, v.d. Mei.